Rediscovering Oyama v. California: At the Intersection of Property, Race, and Citizenship - Rose Cuison Villazor (Washington University Law Review, 2010)
Oyama v. California was a landmark case in the history of civil rights. Decided in January 1948, Oyama held unconstitutional a provision of California's Alien Land Law, which allowed the state to take an escheat action on property given to U.S. citizens that had been purchased by their parents who were not eligible to become citizens. At the time, the country's naturalization law prohibited Japanese nationals from becoming U.S. citizens. Thus, the Alien Land Law applied primarily to Japanese nationals and Japanese Americans. Critically, the Supreme Court in Oyama recognized that the state's attempted taking of a citizen's property because his father was Japanese constituted a violation of his equal protection rights. In so doing, Oyama created a paradigm shift in the treatment of property rights of Japanese Americans. Despite its significance, Oyama has received surprisingly little attention in legal scholarship. Leading constitutional and property law casebooks have virtually ignored the case. This Article seeks to correct that oversight. As this Article argues, Oyama fills a neglected void in our collective historical understanding of race, property law, and citizenship. Equally important, it provides a timely normative and prescriptive response to contentious contemporary debates about the validity of state and local law restrictions on leaseholds against a select group of noncitizens, namely undocumented immigrants. By calling attention to the historical and contemporary contributions of this largely unnoticed case, this Article argues why Oyama should be included in the canons of property and constitutional laws.
Keywords: Property rights; Equal rights; Race discrimination; Emigration & immigration law -- History; Citizenship; Oyama v. California